Bioconversion of used fritters cooking oil derived from palm oil into glycerol and biodiesel / Nuraini Nabilah Sabri - Sabri, Nuraini Nabilah (Faculty of Plantation and Agrotechnology, 2018)
These days, many people use palm oil to fry their food. When they are used, those waste oils are usually thrown away and cause pollution to the environment. One of the ways to treat the waste oil is by converting into biodiesel and glycerol. This research is aimed to study the amount of biodiesel and glycerol that can be produced from 800ml of waste cooking oil. This research was done by transesterification reaction process. The samples were collected from the street sellers in Merlimau Melaka. Methanol was used as a reactant and NaOH was used as a base catalyst. Based on this research, it can be concluded that biodiesel and glycerol made from waste palm oil can be considered a great potential source of commercialization. Based on my experiment, theamount of glycerol and biodiesel in the plastic packaging and bottledpackaging decreasedwhen compared between the new oil to the used oil. The amount of glycerol in new plastic cooking oil is 4.09% and after using the amount decreases to 3.04%. The amount of biodiesel in plastic cooking oil, new plastic oil gets a 54.75% and decreased to 53.5%. For the bottled cooking oil, the result is the same where the amount of glycerol and biodiesel decreasedafter use. The amount is 2.88% for new bottle cooking oil and 2.42% for used bottle cooking oil. Biodiesel in new bottle cooking oil produces 63.63% as compared to used bottle cooking oil which is 58.30%.